1993
DOI: 10.1515/znb-1993-1019
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism Study on Fully Bioactive CCK-Peptides of Increasing Chain Length

Abstract: A CD conformational analysis has been performed on CCK-peptides elongated at the N-terminus in sequence mode beyond the naturally occurring CCK-8 up to the pentadecapeptide sequence. By extending N-terminally the CCK-8 sequence an intramolecular salt bridge between the tyrosine-O-sulfate and the arginine guanido function is allowed to be established. However, this intramolecular electrostatic interaction was not found to affect the bioactivities of the CCK-peptides indicating that induction of such salt bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…A preliminary screening of the conformational preferences of CCK-15 as a function of the environment was performed by means of CD spectroscopy. As reported previously, 10 the spectrum in water lacks any of the features typical of canonical secondary structures, suggesting that CCK-15, like most short linear peptides, assumes a disordered conformation in water. While in surfactants CCK peptides of increasing chain length 10 as well as the lipoderivatized CCK-9 11 were found to exhibit CD spectra typical of β-sheet type structures, in lipid bilayers the lipo-derivatized CCK-9 assumes a helical conformation.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…A preliminary screening of the conformational preferences of CCK-15 as a function of the environment was performed by means of CD spectroscopy. As reported previously, 10 the spectrum in water lacks any of the features typical of canonical secondary structures, suggesting that CCK-15, like most short linear peptides, assumes a disordered conformation in water. While in surfactants CCK peptides of increasing chain length 10 as well as the lipoderivatized CCK-9 11 were found to exhibit CD spectra typical of β-sheet type structures, in lipid bilayers the lipo-derivatized CCK-9 assumes a helical conformation.…”
Section: Resultssupporting
confidence: 73%
“…As reported previously, 10 the spectrum in water lacks any of the features typical of canonical secondary structures, suggesting that CCK-15, like most short linear peptides, assumes a disordered conformation in water. While in surfactants CCK peptides of increasing chain length 10 as well as the lipoderivatized CCK-9 11 were found to exhibit CD spectra typical of β-sheet type structures, in lipid bilayers the lipo-derivatized CCK-9 assumes a helical conformation. 12 Similarly, the CD spectra of CCK-15 recorded in HFA/water (50:50, v/v) shows the double-well shape typical of helical structures.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Using this procedure 1,2-dimyristoyl-3-mercaptoglycerol was linked covalently to the TVa-maleoyl-/3-alanyl derivative of (Thr,Nle)-CCK-9, a fully active CCK analogue (Moroder et al, 1981), to produce the lipophilic CCK adduct (DM-CCK) (Romano et al, 1993b) shown in Figure 1. Since N-terminal derivatization of CCK peptides is not expected to affect significantly their bioactivity profile (Winand et al, 1991a;Moroder et al, 1993a), the lipo-CCK derivative a priori should largely retain its hormonal properties. The lipid-type structure was found to induce self-aggregation of the lipo-CCK derivative on vortexing in aqueous solution with formation of a polydispersed system of unilamellar vesicles.…”
Section: Methodsmentioning
confidence: 99%
“…in 98% TFE (see Figure 4) is characterized by low intensity and despite its difficult interpretation, because of the presence of three aromatic residues in the relatively short sequence, it can be assigned to the presence of y-turn and/or a-helix type ordered structure [42]. Addition of metal ions at increasing concentrations to [Thr,Me]-CCK-9 in 98% TFE leads to a transition from one dominant conformational state to a second one as well evidenced by the isosbestic points at 202-203 and 216-217 nm obtained in both the Ca2+ and Tb3+ titration experiments shown in Figures 4(a) and (b).…”
Section: Binding Of Ca2' and Tb3+ To Gastrin And Cck Peptides In Aquementioning
confidence: 99%